Inhaler Technique Education and Exacerbation Risk in Older Adults with Asthma or Chronic Obstructive Pulmonary Disease: A Meta-Analysis - Maricoto, Tiago (2019)
OBJECTIVES: To evaluate the effect of inhaler education programs on clinical outcomes and exacerbation rates in older adults with asthma or chronic obstructive pulmonary disease (COPD). DESIGN: Systematic review and meta-analysis. SETTING AND PARTICIPANTS: Older adults with asthma or COPD, either in primary or secondary health care and pharmacy setting. MEASUREMENTS: We searched the Medline, Embase, and Central databases according to the main eligibility criteria for inclusion: systematic reviews, meta-analysis, clinical trials and quasi-experimental studies; participants aged 65 and older; education on inhaler technique and reporting of disease control and exacerbation rates. We used the Grading of Recommendations, Assessment, Development and Evaluations scale for quality assessment and used a random-effect model with Mantel–Haenszel adjustment to perform a meta-analysis. RESULTS: We included 8 studies (4 randomized, 4 quasiexperimental) with a total of 1,812 participants. The most frequent type of intervention was physical demonstration of inhaler technique, training with placebo devices. Five studies showed significant reduction in exacerbation rates (pooled risk ratio=0.71, 95% confidence interval=0.59–0.86; p < .001), although effect on disease control and quality of life showed high discrepancy in the reported results, and all randomized studies revealed uncertainty in their risk of bias assessment. CONCLUSION: All interventions seemed to improve inhaler performance and clinically relevant outcomes, but a placebo device could be the most effective. There is evidence that interventions reduce exacerbation risk in older adults, although to an overall moderate degree.